A Three-Phase Grid-Connected PV System Based on SAPF for Power Quality Improvement - Rachid Belaidi; Ali Haddouche; Djamila Ghribi; M. Mghezzi Larafi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper proposes a combined system of three-phase four-wire shunt active power filter (SAPF), and photovoltaic generator (PVG), to solve the power quality problems such as harmonic currents, poor power factor, and unbalanced load. In addition, the proposed system can inject the issued energy from the PVG into the utility grid. To increase the efficiency of the PVG and extract the maximum photovoltaic (PV) power under variable atmospheric conditions, a maximum power point tracking (MPPT) technique based on perturb and observe (P&O) is implemented in the DC/DC boost converter. The effectiveness of the proposed PVG-SAPF (PVG and SAPF) based on the use of synchronous reference frame theory (SRF theory) under unbalanced nonlinear load. The proposed PVG-SAPF is validated through numerical simulations using Matlab/Simulink software. The simulation results show the effectiveness of the proposed PVG-SAPF.